Determinants of Progression of Coronary Artery Calcification in Type 2 Diabetes : Role of Glycemic Control and Inflammatory/Vascular Calcification Markers - VIJAY ANAND, Dhakshinamurthy; LIM, Eric; DARKO, Daniel; BASSETT, Paul; HOPKINS, David; LIPKIN, David; CORDER, Roger; LAHIRI, Avijit (Journal of the American College of Cardiology, 2007)
This study prospectively evaluated the relationship between cardiovascular risk factors, selected biomarkers (high-sensitivity C-reactive protein [hs-CRP], interleukin [IL]-6, and osteoprotegerin [OPG]), and the progression of coronary artery calcification (CAC) in type 2 diabetic subjects. Coronary artery calcification is pathognomonic of coronary atherosclerosis. Osteoprotegerin is a signaling molecule involved in bone remodeling that has been implicated in the regulation of vascular calcification and atherogenesis. Three hundred ninety-eight type 2 diabetic subjects without prior coronary disease or symptoms (age 52 +/- 8 years, 61% male, glycated hemoglobin [HbA(1)c] 8 +/- 1.5) were evaluated serially by CAC imaging (mean follow-up 2.5 +/- 0.4 years). Progression/regression of CAC was defined as a change > or =2.5 between the square root transformed values of baseline and follow-up volumetric CAC scores. Demographic data, risk factors, glycemic control, medication use, serum hs-CRP, IL-6, and plasma OPG levels were measured at baseline and follow-up. Two hundred eleven patients (53%) had CAC at baseline. One hundred eighteen patients (29.6%) had CAC progression, whereas 3 patients (0.8%) had regression. Age, male gender, hypertension, baseline CAC, HbA(1)c >7, waist-hip ratio, IL-6, OPG, use of beta-blockers, calcium channel antagonists, angiotensin-converting enzyme (ACE) inhibitors, statins, and Framingham/UKPDS (United Kingdom Prospective Diabetes Study) risk scores were univariable predictors of CAC progression. In the multivariate model, baseline CAC (odds ratio [OR] for CAC >400 = 6.38, 95% confidence interval [CI] 2.63 to 15.5, p < 0.001), HbA(1)c >7 (OR 1.95, CI 1.08 to 3.52, p = 0.03), and statin use (OR 2.27, CI 1.38 to 3.73, p = 0.001) were independent predictors of CAC progression. Baseline CAC severity and suboptimal glycemic control are strong risk factors for CAC progression in type 2 diabetic subjects.